Changes of occlusal plane inclination after orthodontic treatment with four premolars extraction in dento-alveolar bimaxillary protrusion cases - Zenab, NR Yuliawati; Hambali, Tono S.; Salim, Jono; Mardiati, Endah (Universitas Padjadjaran, 2009)
The purpose of this study was to find out whether there were changes in occlusal plane inclination after fixed orthodontic treatment of bimaxillary protrusion cases where extraction of four first premolars was needed using the standard Edgewise appliances. The sample was fourteen orthodontic patients, aged above sixteen years old, no sexual discrimination, treated with fixed appliances at Orthodontic Specialist Clinic Faculty of Dentistry Universitas Padjadjaran. The method was a pre-post design which compared occlusal plane inclination obtained from tracings of lateral cephalograms before and after orthodontic treatment. The results were calculated with the paired t-test analysis. The study revealed that there were no significant changes in occlusal plane inclination after the orthodontic treatment.